Benefits of physical exercise in pregnancy: an integrative review (Research, Society and Development, 2020)
During pregnancy, women go through several processes in which bodily changes and physiological, biomechanical, metabolic and behavioral adaptations occur. The pregnancy lasts approximately 40 weeks, and promotes changes in the cardiorespiratory, musculoskeletal systems and in general without metabolism in women, these changes cause in women hypertension, gestational diabetes, excessive weight gain, low back and pelvic pain and alteration without balance, in posture and gait, impairing their quality of life. Thus, this study aimed to identify and report the benefits of physical exercise during pregnancy. It is an integrative literature review, with searches in the databases: Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), using the Health Sciences Descriptors (DeCS) “pregnancy” and “physical exercise” and the Boolean operator “AND” at the crossing of words. 13 articles were selected, published between 2000 and 2020 in English and Portuguese. The practice of physical exercises during pregnancy can promote body weight gain and reduced adipose tissue, lower risk of premature delivery, less chances of complications during or immediately after delivery, improvement of the general physical capacity of the physical capacity for delivery, improvement in cardiorespiratory capacity and lower risk or absence of lower limb swelling. It is concluded that physical exercise is relevant, safe and advisable, whether aerobic or even strength, during pregnancy.